A Pseudorandom Binary Generator based on Combination Linear Feedback using Multiplexers and Multivariable Boolean Function - Farías, Andrés Francisco (2024)
In order to produce random or pseudo-random binary sequences, necessary for use in different branches of science such as cryptography, simulation, mathematics, random or pseudo-random binary generators are used. The random strings obtained must have high periods and linear complexity and must pass statistical tests of randomness to ensure that they are effectively random. The development of a generator must take into account the above and be controlled at each stage to obtain a good final result. Simply combining poorly designed cryptographic components can lead to an inadequate generator. This project explains the methodology for developing a reliable binary generator. The basic components of the generator proposed in this presentation are the linear feedback shift registers (LFSR), which due to the linearity of their sequences, requires the use of devices for their combination, such as multiplexers. and Boolean functions to achieve a longer period and have nonlinear behavior in the resulting chain.